Mendorong Pembelian Hijau: Peran Mediasi Brand Image, Trust, dan Loyalty dalam Sustainable Marketing di Body Shop, Malang - Dwi Danesty Deccasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is a quantitative study with a survey approach that aims to examine the indirect effect of Sustainable Marketing on Sustainable Purchasing through the mediating variables of Brand Loyalty, Brand Trust, and Brand Image. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with bootstrapping techniques to test the significance of the relationship between variables. The results of the analysis show that the indirect effect through Brand Loyalty (t = 3.072; p = 0.001) and Brand Trust (t = 2.942; p = 0.002) is significant, proving the effective role of both variables as mediators. Conversely, the indirect effect through Brand Image is not significant (t = 0.675; p = 0.250), indicating that Brand Image does not function as a strong mediating pathway. These findings confirm the importance of Brand Loyalty and Brand Trust in bridging Sustainable Marketing with sustainable purchasing behavior, which emphasizes the importance of building emotional relationships and trust in sustainable marketing strategies.